2002
DOI: 10.1177/073401680202700107
|View full text |Cite
|
Sign up to set email alerts
|

Police Drug Testing, Hair Analysis, and the Issue of Race Bias

Abstract: Poice agents have beg to use hair analysis as a drug-screening tool in both officer recruitment and officer monitoring. This has been controversial because of a putative racial bias associated with human hair specimens, especially focused on cocaine. However, little empirical evidence has been offered to substantiate this claim. To asses this issue, Hoffin (1999, p. 613) analyzed recruitment cohort data from a major metropolitan police department ( N - 1,80) for cocaine ad marijuana hair assays, contrasting re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Analysis of approximately 2,000 hair specimens for a number of drugs, including amphetamines did not support a color effect (Kelly 2000). In other studies, where side-by-side analyses of paired hair and urine specimens of the same individual were performed, was shown that the use of proper methodology provides no statistically significant hair color or hair type effects (Mieczkowski 2002;Cairns 2004b;Cairns 2004c). Consequently, although drugs could bind to melanin in hair, this does not really constitute a problem in hair analysis since, so far, it provides a statistical insignificant effect.…”
Section: Interpretation Of Hair Analysis Resultsmentioning
confidence: 99%
“…Analysis of approximately 2,000 hair specimens for a number of drugs, including amphetamines did not support a color effect (Kelly 2000). In other studies, where side-by-side analyses of paired hair and urine specimens of the same individual were performed, was shown that the use of proper methodology provides no statistically significant hair color or hair type effects (Mieczkowski 2002;Cairns 2004b;Cairns 2004c). Consequently, although drugs could bind to melanin in hair, this does not really constitute a problem in hair analysis since, so far, it provides a statistical insignificant effect.…”
Section: Interpretation Of Hair Analysis Resultsmentioning
confidence: 99%
“…Similar race effects have been found regarding concordance between self-reported drug use and hair assays (Ledgerwood, et al, 2008; Vignali et al, 2012). Such racial disparities may be attributable to over-detecting drug metabolites in African Americans’ hair (Borges et al, 2003; Cone and Joseph, 1996; Fendrich, et al, 2004; Han et al, 2011; Henderson et al, 1998; Kidwell et al, 2000; Kintz et al, 2000; Ledgerwood, et al, 2008; Welp, et al, 2003); however, findings are mixed (Hoffman, 1999; Kelly et al, 2000; Mieczkowski, 2011; Mieczkowski et al, 2002; Mieczkowski and Newel, 2000), and no data have been presented for adults with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Other similar studies also had quite low rates of positive tests. On average, 0,28-0,3 of the total sample showed marihuana or cocaine use (Lersch & Mieczkowski, 2005;Mieczkowski, 2004;Mieczkowski, Lersch & Kruger, 2002). Hoffman (1999) found, however, 1,5% (n=20) of males were positive for cannabis, and 1,2% (n=16) for cocaine.…”
Section: Results: Illicit Substance Abuse In Law Enforcementmentioning
confidence: 99%